The effect of professional fluoride application program for preschool children in Taiwan: An analysis using the National Health Insurance Research Database (NHIRD) - Chia-Ling Hsu; Wei-szu Lin; Ching-Heng Lin; Jengfen Liu (Elsevier, 2018)
Background/Purpose: Dental caries in primary dentition is a major public health problem in many countries, as well as Taiwan. The service of professional topical fluoride application for children under 5 years of age, performed twice a year by the BNHI in Taiwan through the "Preventive Dental Health Service for Children" plan, began in July 2004. The purpose of this study was to examine the effect and trend of professional topical fluoride application on dental utilization. Materials and methods: The sample subjects were taken from the Normalized Million People File of 2010 in the National Health Insurance Research Database from 2000 to 2012, for the purpose of analyzing the status of the professional topical fluoride program. The main analysis included utilization of professional topical fluoride application, utilization of restorative treatment and utilization of endodontic therapy in children 1-to-5-years of age. The Cochran-Armitage trend test was used for statistical analysis. Results: Professional topical fluoride utilization increased year upon year, particularly after 2012 (P < .001). There was a tendency to reduce the utilization of endodontic therapy (P < .001). The severity of dental caries (number of times receiving dental restoration or endodontic therapy) was decreased after professional topical fluoride application was performed (P < .001). Conclusion: Because the dental caries rate for preschool children in Taiwan remains high, it is beneficial to receive professional topical fluoride application for dental care, as this reduces the severity of dental caries and endodontic therapy needs. Keywords: Dental caries, Endodontic therapy, Preschool children, Professional topical fluoride, Restoration treatment